Treatment of anemia in patients with solid tumors receiving chemotherapy in palliative setting: usual practice versus guidelines. Issue 4 (4th July 2018) - de Putter, Robin; Geboes, Karen; De Man, Marc; Van Belle, Simon
ABSTRACT: Background Anemia is frequent in patients with cancer and is often multifactorial. Treatment depends on etiology and can consist of transfusions, intravenous iron (IV Fe), and/or erythropoiesis-stimulating agents (ESA). Several studies have shown that cancer-related anemia is undertreated. The aim of this study is to compare usual practice in a university hospital with the international guidelines. Methods Using the hospital and pharmacy informatics all adults (≥18 years), who received a treatment for anemia (transfusion, IV Fe, ESA) from February to August 2016 during palliative chemotherapy, were identified. Episodes of care were defined as the start of palliative chemotherapy up until 4 weeks after end of chemotherapy. After informed consent, relevant data in the episode of care were collected. Usual practice was compared to international guidelines adapted to Belgium reimbursement criteria. Results A total of 72 episodes of care were included. At initiation of chemotherapy, anemia was present in 59.7% of cases. Iron status was measured in 54.2% of all cases. Iron deficiency was found in 34.7% of patients. Only 52% of the iron deficient patents received IV Fe. Fifteen cases were considered eligible for ESA, six (40%) of these patients received an ESA. The most frequent treatments for anemia were transfusions (91.7%), followed by IV Fe (18.1%). Only 8.3% received an ESA. Conclusion Assessment for iron, Vitamin B12, and FA deficits are underused. We detected a high rate of transfusions. In contrast there is still a low use of IV Fe and ESA's. There has been no major improvement in the implementation of the international guidelines in the last decade. We estimate that in at least 16.7–26.4% of our patients less to no transfusions would have been required, if guidelines were strictly followed.